(untitled) (Research in Agriculture Livestock and Fisheries, 2023)
An experiment was conducted during kharif (summer) season 2021 at the substation of Bangladesh Institute of Nuclear Agriculture (BINA), Gopalganj, Bangladesh. Yield and yield contributing attributes of BINA developed four sesame varieties were observed during the trial. A Randomized Complete Block Design (RCBD) with 3 replications was performed. The varieties were V1 = Binatil-1, V2 = Binatil-2, V3 = Binatil-3 and V4 = Binatil-4. Results from the experiment revealed that plant height, number of branches plant-1, number of pods plant-1, pod length, pod breadth, number of seeds pod-1, 1000 seed weight and seed yield were significantly different among the varieties. The tallest plant (106.00 cm) was found in Binatil-1 while shortest plant (77.33 cm) was observed in Binatil-3. It was observed that Binatil-2 had the foremost branches plant-1 (4.80) while the lowest number of branches plant-1 was found in Binatil-1 (0.33). Moreover, Binatil-3 showed the very best number of pods plant-1 (93.33) while Binatil-1 gave the lowest number of pods plant-1 (47.87). The largest pod was found in Binatil-1 (3.74 cm) while the smallest was found in Binatil-2 (2.42 cm). It had been recorded that Binatil-1 showed the maximum number of seeds pod-1 (76.97) while Binatil-3 gave the minimum number of seeds pod-1 (57.60). The highest number of thousand seed weight was recorded in Binatil-3 (3.12 g) while the lowest thousand seed weight was recorded in Binatil-1 (2.93 g). It had been detected that the variety Binatil-2 showed the highest seed yield (1.35 ha-1) while Binatil-1 gave the lowest seed yield (1.25 ha-1). The remarkable growth and yield performance of sesame from kharif season (summer) trial was observed at Binatil-2. And it will be helpful to select the varieties having high yield potential as well as future breeding materials of sesame in Bangladesh. Vol. 9, No. 3, December 2022: 247-251